1989
DOI: 10.1111/j.1574-6968.1989.tb02437.x
|View full text |Cite
|
Sign up to set email alerts
|

Salmonella typhimurium infection in high and low antibody responder mice: inverse correlation between antibody responsiveness and resistance to infection

Abstract: Susceptibility to Salmonella typhimurium infection was compared in H (high Ab responder) and L (low Ab responder) mice obtained by several selective breeding experiments (Selections I, II, III, IV and IV A) [10,19,22]. H mice were always much more susceptible to infection than their L mice counterparts within a continuous LD 50 variation range. In three of the selections (I, II and IV A) the low responsiveness character is known to result mainly from rapid Ag degradation in L mice macrophages. It was hypothesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
15
0

Year Published

1992
1992
2005
2005

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 17 publications
2
15
0
Order By: Relevance
“…The H mice presented a higher parasite burden in spleen and liver compared to their L counterparts. This result is similar to those obtained when the lines H and L were used as experimental models for other intracellular parasites such as Leishmania tro p i c a 4 a n d Salmonella typhimurium 24 and Brucella suis 11 . In our model we observed that after 20 and 30 days H mice were more susceptible than L mice since H mice showed a significantly higher number of parasites both in spleen and liver.…”
Section: Acute Growth Rate Of L Donovani In H and L Mice From Selectsupporting
confidence: 86%
“…The H mice presented a higher parasite burden in spleen and liver compared to their L counterparts. This result is similar to those obtained when the lines H and L were used as experimental models for other intracellular parasites such as Leishmania tro p i c a 4 a n d Salmonella typhimurium 24 and Brucella suis 11 . In our model we observed that after 20 and 30 days H mice were more susceptible than L mice since H mice showed a significantly higher number of parasites both in spleen and liver.…”
Section: Acute Growth Rate Of L Donovani In H and L Mice From Selectsupporting
confidence: 86%
“…14 Outbred mice selected for high or low quantitative antibody response to Salmonella flagellar antigens 9 (Selection III) are very different in terms of antibody production to various unrelated antigens (multispecific effect), indicating that the general mechanisms of antibody synthesis have been modified in these lines. 15 High (HIII) and low (LIII) responder mice also differ in susceptibility to Salmonella enterica serotype Typhimurium infection 11 and skin tumorigenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Mice bidirectionally selected for high (H) or low (L) antibody production against diverse antigens 8,9 have been important tools for the understanding of the genetic regulation of the humoral immune response and its influence in processes as diverse as susceptibility to bacterial infection, 10,11 experimental arthritis, 12 , longevity 13 and chemical tumorigenesis. 14 Outbred mice selected for high or low quantitative antibody response to Salmonella flagellar antigens 9 (Selection III) are very different in terms of antibody production to various unrelated antigens (multispecific effect), indicating that the general mechanisms of antibody synthesis have been modified in these lines.…”
Section: Introductionmentioning
confidence: 99%
“…Macrophages of L mice presented high catabolism of the immunogens with consequent deficiency in their antigen presentation function leading to a low antibody production. These animals, however, have shown a higher resistance to intracellular pathogens compared to H mice whose macrophage are less catabolic, leading to a high antibody production and greater susceptibility to these pathogens (5,7,8,38).…”
mentioning
confidence: 99%
“…Since R. equi is a facultative intracellular parasite, and L IV-A mice have been described as more resistant than H IV-A mice to intracellular pathogens (5,8,38,41), the Selection IV-A was considered an appropriated model to understanding innate immunity events, especially the role of activated macrophage to rhodococosis resolution. The objective of this study was to investigate immune response events and the macrophage activity of H IV-A and L IV-A mice in R. equi infection.…”
mentioning
confidence: 99%